Secondary tuberculosis of adjacent segments after anterior cervical discectomy and fusion: A case report - Liu, Chengjiang; Liu, Yidong; Ma, Boyuan; Zhou, Mengmeng; Zhao, Xinyan; Fu, Xuanhao; Kan, Shunli; Hu, Wei; Zhu, Rusen (Frontiers in Surgery, 2023)
Introduction: Anterior cervical discectomy and fusion (ACDF) is a common operation for spinal surgery to treat a variety of cervical diseases. The postoperative infection rate of this procedure is extremely low, and adjacent segments are rarely involved. Tuberculosis (TB) is a common infectious disease that affects the spine in less than 1% of cases and is more common in the thoracolumbar and rarely cervical spine. Herein, for the first time, we report tuberculosis infection in adjacent segments after ACDF. Case presentation: We report a 50-year-old patient with cervical spondylotic myelopathy (CSM) who was discharged from the hospital after receiving ACDF at the C3/4 level. Two months later, he was admitted to the hospital with neck pain and found to be infected with tuberculosis in C4/5. After four months of anti-tuberculosis treatment, the vertebral body was fused. Conclusion: After ACDF, the adjacent cervical vertebrae were infected with TB but the infection was limited. We believe that the special vertebral blood supply and postoperative secondary blood-borne infection may lead to the occurrence of extrapulmonary tuberculosis.